Writing black Scotland race, nation and the devolution of black Britain - Jackson, Joseph H. (Edinburgh University Press, 2020)
New readings of contemporary Scottish writing with a particular focus on race and racism. A critical approach to blackness in devolutionary Scottish writing. Analysis of the implications of 'black Scotland' for the larger formation of 'black Britain'. Writing Black Scotland examines race and racism in devolutionary Scottish literature, with a focus on the critical significance of blackness. The book reads blackness in Scottish writing from the 1970s to the early 2000s, a period of history defined by post-imperial adjustment. Critiquing a unifying Britishness at work in black British criticism, Jackson argues for the importance of black politics in Scottish writing, and for a literary registration of race and racism which signals a necessary negotiation for national Scotland both before and after 1997
Keywords: Geschichte 1970-2020; Schwarze; Englisch; Literatur; Schottland; English literature / Black authors / History and criticism; English literature / Scottish authors / History and criticism; English literature / 20th century / History and criticism; Blacks in literature; Blacks / Scotland / Social conditions; Blacks / Social conditions; English literature; English literature / Black authors; English literature / Scottish authors; Scotland; 1900-1999; Criticism, interpretation, etc